Marketing Strategy for Meatball Sellers in Pekanbaru in Increasing Profitability - Witjakso, Ario; Ardan Mardan, Jhonni; Amos, Amos; Medina Dzikra, Faira; Hidayat, Muhammad (Lafadz Jaya Publisher, 2023)
This research is motivated by the marketing strategy used by meatball sellers in Pekanbaru to increase profitability. Information regarding interesting marketing strategies implemented by meatball sellers in Pekanbaru already involves elements of sharia marketing. The objectives of this research are: 1) Analyzing the marketing strategies of meatball sellers in Pekanbaru to increase their profitability. 2) Analyze the impact of marketing strategies implemented by meatball sellers in Pekanbaru in increasing profitability. This research includes field study research, in the implementation process, this research uses a qualitative descriptive approach that focuses the study on product marketing and pricing. Data was collected using the interview method with meatball shop informants in Pekanbaru, observation and documentation in the Bakso Shop environment in Pekanbaru, then the data was processed and then analyzed using descriptive-qualitative methods. Based on the results of research that has been carried out regarding the marketing strategy of meatball sellers in increasing profitability from a Sharia economic perspective, the conclusions obtained are 1) Marketing strategy for Product, Price, Promotion, Distribution, Place, People, Process and Physical Evidence are used to analyze and determine business policies to attract consumer interest and satisfaction. 2) Analyzing the impacts that occur with the existence of the meatball business, the impacts are divided into two types, namely positive and negative impacts, the positive impact is family and community income, while the negative impact is the influence of imported meat ingredients and the increase in basic prices which reduces income.